2020
DOI: 10.1101/2020.07.22.20160259
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Circulating cytokines and lymphocyte subsets in patients who have recovered from COVID-19

Abstract: To investigate the immune status of people who previously had COVID-19 infections, we recruited patients 2 weeks post-recovery and analyzed circulating cytokines and lymphocyte subsets. We measured levels of total lymphocytes, CD4+ T cells, CD8+ T cells, CD19+ B cells, CD56+ NK cells, and the serum concentrations of interleukin (IL)-1, IL-4, IL-6, IL-8, IL-10, transforming growth factor beta (TGF-β), tumor necrosis factor alpha (TNF-α), and interferon gamma (IFN-γ) by flow cytometry. We found that in most post… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
(26 reference statements)
1
2
0
Order By: Relevance
“…Patients infected with the SARS-COV-2 (Qin et al, 2020;Wan et al, 2020), SARS-COV (Huang et al, 2005), H7N9 (Zhou et al, 2013) and H5N1 (Henter et al, 2006) were found to have increased levels of cytokines (especially IL-6) which indicated an uncontrolled systemic inflammatory reaction process, and might lead to severe immune pathological damage. Similar to the present study, a study in China demonstrated that two weeks post recovery, patients with COVID-19 had elevated levels of IL-6 (20.59%), IL-4 (19.12%), TNF-α (10.29%), IL-17 (2.94%) and IL-10 (1.47%) while levels of cytokine in healthy controls were all in normal ranges (Hasichaolu et al, 2020). Another study in China compared the levels of cytokines in hospitalized and discharged patients with non-critical COVID-19, it reported that the levels of IL-6, TNF-α, IFN-γ, IL-2, IL-4, and IL-10 were all upregulated in the hospitalized patients (Lin et al, 2020).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Patients infected with the SARS-COV-2 (Qin et al, 2020;Wan et al, 2020), SARS-COV (Huang et al, 2005), H7N9 (Zhou et al, 2013) and H5N1 (Henter et al, 2006) were found to have increased levels of cytokines (especially IL-6) which indicated an uncontrolled systemic inflammatory reaction process, and might lead to severe immune pathological damage. Similar to the present study, a study in China demonstrated that two weeks post recovery, patients with COVID-19 had elevated levels of IL-6 (20.59%), IL-4 (19.12%), TNF-α (10.29%), IL-17 (2.94%) and IL-10 (1.47%) while levels of cytokine in healthy controls were all in normal ranges (Hasichaolu et al, 2020). Another study in China compared the levels of cytokines in hospitalized and discharged patients with non-critical COVID-19, it reported that the levels of IL-6, TNF-α, IFN-γ, IL-2, IL-4, and IL-10 were all upregulated in the hospitalized patients (Lin et al, 2020).…”
Section: Discussionsupporting
confidence: 89%
“…In addition to our previous study, there were also other researches indicating that the immune system gradually recovered after COVID-19 infection. A study in China found decreased levels of CD8 + T cells, CD19 + B cells, total lymphocytes, CD3 + T cells, CD4 + T cells and CD56 + NK cells in COVID-19 patients two weeks post recovery (Hasichaolu et al, 2020). Another study in China suggested that the levels of neutrophils, monocytes, NK cells, and CD4 + T cells increased, and levels of total lymphocytes and CD8 + T cells significantly decreased in discharged non-critical patients with COVID-19 than those hospitalized (Lin et al, 2020).…”
Section: Discussionmentioning
confidence: 97%
“…В связи с этим авторы считают, что повышенные уровни указанных цитокинов являются независимыми предикторами эффективности реабилитации. Эти результаты также показывают постепенное восстановление иммунной системы после перенесенного COVID-19, а устойчивый гипервоспалительный ответ, обусловленный цитокинами, более 14 дней предполагает необходимость продолжения медицинского наблюдения после выписки из стационара, но для полного понимания последствий COVID-19 в аспекте цитокиновых нарушений, по мнению авторов, необходимы лонгитюдинальные исследования выздоровевших пациентов [14].…”
Section: Discussionunclassified
“…There was a study founded that the value of IL-6 remains high after infection with Covid-19 disease, and the explanation for this might be that postrecovery declines in lymphocyte subsets and elevations in cytokines have been found as independent predictors of rehabilitation success (40).…”
Section: Discussionmentioning
confidence: 99%